Personal comorbidities and their subsequent risks for liver, gallbladder and bile duct cancers - Hemminki, Kari; Sundquist, Kristina; Sundquist, Jan; Försti, Asta; Liska, Vaclav; Hemminki, Akseli; Li, Xinjun (International journal of cancer, 2023)
Many environmental risk factors for hepatobiliary cancers are known but whether they are associated with specific cancer types is unclear. We present here a novel approach of assessing standardized incidence ratios (SIRs) of previously diagnosed comorbidities for hepatocellular carcinoma (HCC), gallbladder cancer (GBC), cholangiocarcinoma (CCA) and ampullary cancer. The 13 comorbidities included alcohol and nonalcohol related liver disease, chronic obstructive pulmonary disease, gallstone disease, viral and other kinds of hepatitis, infection of bile ducts, hepatic and other autoimmune diseases, obesity and diabetes. Patients were identified from the Swedish Inpatient Register from 1987 to 2018, and their cancers were followed from 1997 onwards. SIRs for HCC were 80 to 100 in men and women diagnosed with hepatitis C virus and they were also >10 in patients diagnosed with hepatitis B virus, other kind of hepatitis, hepatic autoimmune disease and nonalcohol related liver disease. Many of these risks, as well as alcohol related liver disease, were either specific to HCC or were shared with intrahepatic CCA. For GBC, CCA and ampullary cancer infection of bile ducts was the main risk factor. Gallstone disease, nonhepatic autoimmune diseases and diabetes were associated with all hepatobiliary cancers. The limitations of the study include inability to cover some rare risk factors and limited follow-up time. Many of the considered comorbidities are characterized by chronic inflammation and/or overt immune disturbance in autoimmune diseases. The results suggest that local chronic inflammation and a related immune disturbance is the carcinogenic trigger for all these cancers.
Keywords: familial risk; nádory ductus choledochus; autoimunitní nemoci; nádory žlučových cest; Male; nádory jater; žlučové cesty intrahepatální; lidé; nádory žlučníku; Carcinoma, Hepatocellular; Autoimmune Diseases; Humans; comorbidity; ampulla Vateri; cholangiokarcinom; alcohol; zánět; Gallbladder Neoplasms; smoking; risk factor; Bile Duct Neoplasms; hepatocellular carcinoma; Bile Ducts, Intrahepatic; hepatocelulární karcinom; mužské pohlaví; cholelitiáza; Common Bile Duct Neoplasms; Cholelithiasis; Liver Neoplasms; ženské pohlaví; Inflammation; Female; Cholangiocarcinoma; Ampulla of Vater